Identification of external branch of superior laryngeal nerve in relation to upper pole of thyroid gland in thyroid surgery - Barman, Sanjib; Bhattacharjee, Abhinandan; Dutta, Smrity Rupa Borah (International Journal of Research in Medical Sciences, 2024)
Background: One of the most common procedures carried out by otorhinolaryngologists is thyroidectomy. A challenging aspect of thyroid surgery is the prevention of damage to the external branch of the superior laryngeal nerve (EBSLN). The objective of this study is to assess the rate of identification and different anatomical variations of the EBSLN in relation to the upper pole of the thyroid gland during thyroidectomy operation. Methods: This is a prospective observational study conducted in the Department of Otorhinolaryngology, Silchar Medical College and Hospital, Silchar, Assam involving 25 patients who underwent thyroidectomy between January 2023, and December 2023. The study included patients aged 20 years and older who fulfilled the specified inclusion and exclusion criteria. The traditional open thyroidectomy technique was used for each procedure, using a standard Kocher's skin incision. We categorised the anatomical course of the EBSLN in relation to upper pole of the thyroid gland. Results: In this study, out of the 29 EBSLN, 24 (82.35%) nerves were successfully identified, whereas 5 (17.64%) nerves could not be identified. Out of 24 EBSLN, we found 20 (68.97%) nerves crossing superior thyroid vessels above the upper pole of the thyroid gland and 4 (13.79%) nerves crossing underneath the upper pole of the thyroid gland. Conclusions: We should direct our dissection more carefully in the region above the upper pole of the thyroid, as the majority of EBSLN crosses the superior thyroid vessels above the upper pole of the thyroid gland. We should also avoid extensive dissection in search of EBSLN, keeping in mind that some nerve branches that cross the superior thyroid vessels under the cover of the upper pole of the thyroid gland put patients at greater risk for injury during thyroidectomy.